2011
DOI: 10.1007/s10646-011-0726-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an anionic surfactant (FFD-6) on the energy and information flow between a primary producer (Scenedesmus obliquus) and a consumer (Daphnia magna)

Abstract: The effects of a commercially available anionic surfactant solution (FFD-6) on growth and morphology of a common green alga (Scenedesmus obliquus) and on survival and clearance rates of the water flea Daphnia magna were studied. The surfactant-solution elicited a morphological response (formation of colonies) in Scenedesmus at concentrations of 10–100 μl l−1 that were far below the No Observed Effect Concentration (NOEC) value of 1,000 μl l−1 for growth inhibition. The NOEC-value of FFD-6 for colony-induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
(68 reference statements)
2
15
0
Order By: Relevance
“…The FFD-6 drastically depressed the feeding and survival rates of D. magna. The LC 50 -24 h and LC 50 -48 h were respectively 148 μl/L and 26 μl/L [248].…”
Section: Infochemicalsmentioning
confidence: 92%
“…The FFD-6 drastically depressed the feeding and survival rates of D. magna. The LC 50 -24 h and LC 50 -48 h were respectively 148 μl/L and 26 μl/L [248].…”
Section: Infochemicalsmentioning
confidence: 92%
“…Whereas no significant differences in feeding rates could be detected for diuron-and paraquat-exposed compared with control algae, pre-exposure to S-metolachlor reduced feeding by rotifers in a dose-dependent manner (Fig. A similar correlation between feeding rates and particle size was also observed for green algae exposed to the anionic surfactant FFD-6 and the predator D. magna, indicating that chemical effects on particle size might be a more general mechanism for how toxicants can interact with such food webs [27]. This finding shows that S-metochlor-treated algae are indeed less palatable for rotifers.…”
Section: Sequential Exposure To Herbicide and Predation Stressmentioning
confidence: 58%
“…Several studies have investigated the influence of predation on pesticide tolerance in freshwater cladocerans [6,[15][16][17], amphibians [18][19][20], and insects [21][22][23]. One example of chemicalinduced tolerance to predation was recently presented by Lürling et al for the green alga Scenedesmus obliquus: the anionic surfactant FFD-6 induced a response in the alga that protected it from being grazed by the water flea D. magna [27]. However, most of the studies investigated predation stress only by adding chemical signals released by predators into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of feeding has been applied by several authors to assess the possible ecotoxicological effects of different contaminants, such as metals (Flickinger et al, 1982;Ferrando and Andreu, 1993) and pesticides (Fernandez-Cassalderrey et al, 1994). Hartgers et al (1999) and Lürling et al (2011) found that the clearance rate of Daphnia magna using artificial beads is a more sensitive endpoint than an acute lethal test. Alterations in the feeding and digestive behaviour of daphnids as endpoints were compared by De Coen and Janssen (1998) and , where ingestion rate was assessed using fluorescent microbeads and measuring fluorescence.…”
Section: Discussionmentioning
confidence: 99%